2022
DOI: 10.1002/adfm.202207960
|View full text |Cite
|
Sign up to set email alerts
|

Superior Room Temperature Compressive Plasticity of Submicron Beta‐Phase Gallium Oxide Single Crystals

Abstract: Bulk‐scale (2¯$\bar{2}$01)‐oriented monoclinic beta‐phase gallium oxide (β‐Ga2O3) single crystals are brittle and fracture at low compressive strains. Here, it is reported that submicron β‐Ga2O3 pillars exhibit an exceptional room temperature plastic strain of up to ≈22% under compression. Deformation is observed in transition from brittle to superior plasticity with reduction of pillar size. The critical diameter for the brittle to ductile transition is ≈800 nm, attributed to the initiation of dislocation sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Typically, nanoindentation tests 41 and micro‐/nanopillar tests 82 are employed to understand the plastic behavior (very often accompanied by cracking). For instance, quite some studies are published in the last two decades on micro‐/nanopillar compression, addressing the plastic deformation of carbides, 111 oxides, 112,113 and mainstream semiconductors such as Si 114 and GaAs 115 . A common observation is that, once the diameter of the pillars decreases below a critical value (e.g., ∼300 nm for Si 116 and ∼150 nm for dislocation‐free SrTiO 3 117 ]), plasticity sets in without fracturing the pillars and a large plastic strain can be achieved.…”
Section: Dislocation Engineering In Ceramicsmentioning
confidence: 99%
“…Typically, nanoindentation tests 41 and micro‐/nanopillar tests 82 are employed to understand the plastic behavior (very often accompanied by cracking). For instance, quite some studies are published in the last two decades on micro‐/nanopillar compression, addressing the plastic deformation of carbides, 111 oxides, 112,113 and mainstream semiconductors such as Si 114 and GaAs 115 . A common observation is that, once the diameter of the pillars decreases below a critical value (e.g., ∼300 nm for Si 116 and ∼150 nm for dislocation‐free SrTiO 3 117 ]), plasticity sets in without fracturing the pillars and a large plastic strain can be achieved.…”
Section: Dislocation Engineering In Ceramicsmentioning
confidence: 99%
“…The streaking of the diffraction spots in the FFT pattern (Fig. 8e, insert) suggested that a high density of stacking faults (SFs) was also generated within the nanoparticle [30].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…9), abundant lattice ceramic and they thought that the SFs were actually formed at high temperatures due to drastic plastic deformation and the rapid cooling process "froze" the SFs [36]. Wu et al found that a large number of SFs were formed during the compression of single crystal β-Ga2O3, which enabled the material to obtain room temperature plasticity [30].…”
Section: J U S T a C C E P T E Dmentioning
confidence: 99%
“…al. [5] reported a brittle to plastic transition during compressive deformation at room temperature for monoclinic beta-phase gallium oxide (𝛽-Ga 2 O 3 ) single crystals with reduction of the pillar size below 800 nm. Mignerot et al [6] observed plastic deformation of InSb micronsized pillars during microcompression tests at room temperature and found stress-induced nano-twin formation.…”
Section: Introductionmentioning
confidence: 99%
“…al. [ 5 ] reported a brittle to plastic transition during compressive deformation at room temperature for monoclinic beta‐phase gallium oxide (β‐Ga 2 O 3 ) single crystals with reduction of the pillar size below 800 nm. Mignerot et al.…”
Section: Introductionmentioning
confidence: 99%